Efficacy of Trichoderma spp. and fungicides against Lasiodiplodia theobromae - Bhadra, Mousumi; Khair, Abul; Hossain, Md Anawar; Sikder, Md Maniruzzaman (Bangladesh Journal of Scientific and Industrial Research, 2015)
Experiments were carried out to find out the bio-efficacy of four Trichoderma species, viz. Trichoderma harzianum, T.koningii, T.viride (green strain), T.viride (yellow strain) against canker pathogen Lasiodiplodia theobromae. Bioassay of antagonist against test pathogens conducted by dual culture techniques at different temperatures; volatile, non volatile and naturally untreated metabolites of isolates were examined. T. koningii and T.viride (yellow strain) exhibited maximum inhibition in controlling the pathogens. Fungicides, viz. Bavistin and Dithane M-45 used where Bavistin found little effective but Dithane M-45 showed no effects on pathogen. Trichoderma viride showed better performance to control Lasiodiplodia theobromae than commercial fungicides used during present investigation. DOI: http://dx.doi.org/10.3329/bjsir.v49i2.22008 Bangladesh J. Sci. Ind. Res. 49(2), 125-130, 2014